Hypertonic Saline Nasal Irrigation for Chronic Sinusitis: A Systematic Review and Meta-analysis - Alexsandro Lao; Akhil Vatvani; Ni Putu Setiawathi (PERHATI-KL, 2023)
Background: Chronic rhinosinusitis (CRS) is an inflammatory condition of the paranasal sinusescharacterized by persistent sinonasal symptoms. It is a prevalent chronic medical ailment worldwide,impacting individuals of all ages and impairs patients’ quality of life. Recent findings in otorhinolaryngology reveal that hypertonic saline nasal irrigation is more effective than isotonic saline for addressing this condition. Hypertonic saline with higher osmotic pressure demonstrates superior efficacy in reducing mucosal edema. Purpose: To study the efficacy of nasal irrigation with hypertonic saline on chronicrhinosinusitis. Literature review: Conducted following the Preferred Reporting Items for SystematicReview and Meta-Analysis (PRISMA) 2020 guidelines. The search strategy spanned prominent multipleelectronic databases (PubMed and SagePub), encompassing publications from 2015 to 2023. Duplicatepublications, review articles, and incomplete articles were excluded. A meta-analysis was planned toanalyze outcome of Visual Analog Scale (VAS) score. Result: The search results from the year 2015-2023 yielded 35 articles from PubMed and 28 articles from SagePub. In the end, 4 eligible studies wereobtained. From these, hypertonic saline demonstrated enhanced symptomatic relief. However, only twostudies were eligible for meta-analysis, revealing no significant VAS difference between hypertonic andnormal saline (mean difference 2.40 [95% CI -2.85 – 7.65]; p 0.37). Conclusion: Hypertonic saline nasal irrigation offered moderate side effects, improved nasal symptoms and ciliary activity more than isotonic saline, although there were no significant differences in radiological imaging or sense of smell. However, the meta-analysis did not find a significant difference in VAS scores.Keywords: chronic rhinosinusitis, ciliary activity, nasal irrigation, hypertonic saline